1987
DOI: 10.1088/0029-5515/27/11/012
|View full text |Cite
|
Sign up to set email alerts
|

Profile consistency on TFTR

Abstract: Electron heat transport on TFTR and other tokamaks is several orders of magnitude larger than neoclassical calculations predict. Despite considerable effort, there is still no clear theoretical understanding of this anomalous transport. The electron temperature profile, Te(r), has shown a marked consistency on many machines for a wide range of plasma parameters and heating profiles. This could be an important clue as to the process responsible for this enhanced thermal transport. In the first section of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 19 publications
6
21
0
Order By: Relevance
“…13 for the case of carbon pellet perturbations. That study confirmed profile resiliency of the electron temperature 14 following the pellet, in addition to observing that the electron stored energy actually increases transiently as a result of the perturbation. Most interesting, however, was that in contrast with the large degradation and slow recovery suffered by supershots, L-Mode plasmas suffered no loss of stored energy during deep carbon pellet perturbations.…”
Section: Introductionsupporting
confidence: 74%
“…13 for the case of carbon pellet perturbations. That study confirmed profile resiliency of the electron temperature 14 following the pellet, in addition to observing that the electron stored energy actually increases transiently as a result of the perturbation. Most interesting, however, was that in contrast with the large degradation and slow recovery suffered by supershots, L-Mode plasmas suffered no loss of stored energy during deep carbon pellet perturbations.…”
Section: Introductionsupporting
confidence: 74%
“…These measurements are the second harmonic electron cyclotron black-body emission as measured by a Michelson interferometer [51] and are averaged over a couple of sawtooth periods. Further, it is shown elsewhere [7,8,56] that the normalized TFTR temperature profiles (i.e. T e (r)/T e (0) versus r/a) are invariant whether the discharge is heated ohmically or with additional low-power neutral beam heating.…”
Section: Fig 4 Comparison Of [{T E )/T Eo L Ex P With [(T E )/T El ]^...mentioning
confidence: 99%
“…NUCLEAR FUSION, Vol.30, No. 10 (1990) In the literature, many authors [2][3][4][5][6][7][8][9][10][11][12][13] have proposed various different profile shapes to explain (either directly or indirectly) some or all of the observed general features of profile consistency. 1 The primary objective of some of these models was to understand the nature of the energy and particle transport processes in tokamak plasmas, while others concentrated on understanding the macroscopic stability of the plasma column for magnetohydrodynamic (MHD) modes (for example, via the minimum energy principle and the principle of minimum entropy production), with profile consistency as a by-product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The a 2 dependence and the numerical factors in Eqs. (6) and 7are result* of the cylindrical approximation and the use of thermal diffusivities measured in a limited range of parameters.…”
Section: Eq (3) Asmentioning
confidence: 99%